Effective-Medium Characteristics of Reflective Metasurface: A Quasi-One-Port Network Theory - Feng-Yuan Han; Fan-Hong Li; Jiang-Yu Liu; Pu-Kun* Liu (IEEE Transactions on Microwave Theory and Techniques, 2019)
Reflective metasurfaces are utilized as a bridge linking propagating waves and surface waves. However, the effective constitutive parameters (permittivity and permeability) cannot be retrieved by conventional theory without transmission coefficients. In this paper, an innovative method based on a quasi-one-port network model is proposed to robustly retrieve the effective electromagnetic parameters (εeff, μeff, neff, and zeff) for reflective metasurfaces with isotropic unit cells. The validity of the method is demonstrated by imping TE-polarized terahertz waves normally and obliquely (10°) on the multiple-layer unit cells. The effective boundary of the multiple-layer cells is determined by minimizing the deviation of the effective refractive indices from 0.1018 to 0.0260 using a genetic algorithm, which increases the consistency of the retrieval results. The sensitivity of the effective constitutive parameters to the accuracy of reflection coefficients and nonzero incident angle θi is also discussed. This method is beneficial for the design of reflective metasurfaces or multichannel reflectors, the coupling of spoof space plasmon polaritons, and other applications of anomalous reflection.